DETERMINASI INFLASI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) TAHUN PERIODE 2017-2021 - Agung Budi (Universitas Muhammadiyah Tangerang, 2022)
This study aimed to determine the effect of the rupiah exchange rate and inflation on the composite stock price index (CSPI) on the Indonesia stock exchange (IDX). The period used in this study is 5 (five) years, starting from 2017-2021.This study uses a quantitative approach. Population and sample are taken from all data at the end of the JCI month, rupiah exchange rate and inflation in the 2017-2021 period using saturated sampling technique. The data analysis technique used is multiple linear regression.The results showed that the rupiah exchange rate partially had not significant effect on the composite stock price index (CSPI) indicated by the t value <t table (0.901483 <2.00247) and the significance of 0.3711> 0.05. For the inflation variable partially negative and significant effect on the composite stock price index (CSPI) is indicated by the value of t count <t table (-4.135408 <-2.00247) and a significance of 0.0001 <0.05. Simultaneously the rupiah exchange rate and inflation influence and significant effect on the composite stock price index shown by the calculated F value> F table (16.21406> 3.16) and a significance of 0.000003 <0.05. The ability of the rupiah exchange rate variable and inflation in explaining the stock price index (IHSG) of 34.02% as indicated by the size of the adjusted R square of 0.3402 while the remaining 65.98% is influenced by other factors not examined in this study. With the value of the multiple linear regression equation Y = 523,991 - 0,072912 NTR - (-182,3542) INF + e Keywords: Composite Stock Price Index (CSPI), Rupiah Exchange Rates, Inflation